Health knowledge, DHF risk, clean and healthy living behavior: A social psychology study in a highland community - Cerlyawati, Hugi; Indrawati, Endang Sri; Prasetyo, Anggun Resdasari; Ahmed, Faisal (Faculty of Psychology, Universitas Diponegoro, 2025)
Background: Dengue Hemorrhagic Fever (DHF) is closely linked to environmental conditions and human behavior. In highland areas, geography, knowledge, and community values influence clean and healthy living practices. However, actual behavior in the field does not always match the level of understanding.Purpose: To analyze the effect of knowledge and DHF risk on healthy house conditions as a representation of healthy living behavior in a highland village community.Method: An observational analytical study with a cross-sectional design involving 335 respondents selected through simple random sampling. Data were collected using questionnaires and analyzed using Structural Equation Modeling-Partial Least Square (SEM-PLS).Findings: Although 86.6% of respondents had good knowledge about healthy houses, only 52.5% lived in healthy house conditions. Knowledge significantly influenced healthy house conditions directly (t=3.214) and indirectly through DHF risk (t=2.771). DHF risk also had a significant effect (t=2.260). Demographic factors (education, occupation, gender) showed no significant influence. Field observations indicated generally good waste management, though gaps remained between knowledge and practice.Implication: Community knowledge is essential but insufficient alone. Community-based interventions and empowerment initiatives are needed to strengthen sustainable healthy living behaviors and support DHF prevention